2015
DOI: 10.1373/clinchem.2014.233312
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fetal Subchromosomal Abnormalities by Sequencing Circulating Cell-Free DNA from Maternal Plasma

Abstract: BACKGROUND:The development of sequencing-based noninvasive prenatal testing (NIPT) has been largely focused on whole-chromosome aneuploidies (chromosomes 13, 18, 21, X, and Y). Collectively, they account for only 30% of all live births with a chromosome abnormality. Various structural chromosome changes, such as microdeletion/microduplication (MD) syndromes are more common but more challenging to detect. Recently, several publications have shown results on noninvasive detection of MDs by deep sequencing. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
167
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(175 citation statements)
references
References 32 publications
3
167
0
5
Order By: Relevance
“…Expanding NIPS to include detection of specific conditions caused by a CNV (e.g., 22q11.2 deletion, 1p36 deletion, 15q11.2-13 deletion) is technically possible (analytical validity). [60][61][62][63] The phenotypes associated with these conditions can be severe; therefore, they may be appropriate conditions for prenatal screening. However, providers and patients must be aware that expanding the use of NIPS to include the detection of CNVs requires in-depth knowledge of the limitations of the technology, return of results, and follow-up.…”
Section: Acmg Statement Should Nips Be Offered For Detection Of Copy mentioning
confidence: 99%
See 1 more Smart Citation
“…Expanding NIPS to include detection of specific conditions caused by a CNV (e.g., 22q11.2 deletion, 1p36 deletion, 15q11.2-13 deletion) is technically possible (analytical validity). [60][61][62][63] The phenotypes associated with these conditions can be severe; therefore, they may be appropriate conditions for prenatal screening. However, providers and patients must be aware that expanding the use of NIPS to include the detection of CNVs requires in-depth knowledge of the limitations of the technology, return of results, and follow-up.…”
Section: Acmg Statement Should Nips Be Offered For Detection Of Copy mentioning
confidence: 99%
“…Validation studies make the point that DR and SPEC depend on many variables (e.g., depth of read), 10,[60][61][62][63] which can change the false-positive and false-negative rate when NIPS is used for prenatal detection of CNVs. Pretest and posttest counseling is further confounded by variable expressivity and penetrance of the conditions being screened, size of the deletion being screened, specific genes within the critical region of the locus interrogated, and the number of genes within the critical region being screened.…”
Section: Acmg Statement Should Nips Be Offered For Detection Of Copy mentioning
confidence: 99%
“…Reports from reference laboratories have been broadly consistent with the estimates of detection rates (DRs) and false-positive rates (FPRs) established in these trials [2][3][4][5][6]. Additionally, both proof of principle [7][8][9] and data from reference laboratories [10,11] have indicated that screening is possible for select sets of microdeletion syndromes.…”
Section: Introductionmentioning
confidence: 53%
“…Schématique-ment, une lecture correspond à un fragment séquencé), ce qui est très onéreux [14]. Depuis, diverses équipes ont publié des cas de microdélétions/microduplications détectées par MPS de l'ADNfc avec une diminution du nombre de lectures nécessaires et donc du coût, et ce, grâce à des améliora-tions techniques (séquençage ciblé) [21,22] ou bioinformatiques [23] (Tableau 3). Les données publiées à ce jour concernent diverses régions chromosomiques et restent insuffisantes pour évaluer les performances des différentes approches proposées pour chaque anomalie.…”
Section: Anomalies Subchromosomiquesunclassified